(untitled) (Journal of Computational Mathematics, 2021)
In this paper we investigate three various algorithms for computation of generalized inverses which are contained in the limit expressions lim_z→0 V (DT + zI)^-l U and lim_z→0 V (DT + zI)^-l Z^e. These algorithms are extensions of the algorithms developed by various authors in [2], [3-4], [7-9], [16-18].